Beef Cow-Calf Enterprise - Fausett, Marvin R.; Jones, Rodney D. (My University, 1997)
This publication provides a budget based on projected input and output prices. This budget is based on a typical spring calving cow herd with natural breeding.
MF266_1997_10
Keywords: MF266; Livestock; Economics; MF